Efecto del porcentaje de ácido acético en la vida útil de una conserva de pollo desmenuzado en escabeche - Torres Intriago, Carlos Asisclo (2019)
The objective of the present investigation was to evaluate the effect of acetic acid on the shelf life of a pickled chicken conserved according to the storage temperature and different percentages of preservative. Storage was studied at 35 and 45 ° C, four percentages of acetic acid (4, 5, 6 and 7). Sensory parameters (color, odor, taste, texture and acceptability), chemical (pH and sodium chloride) and microbiological parameters (Mesophilic Aerobics, Escherichia Coli, Staphilococus Aureus and Salmonella spp) were evaluated. The acceleration factor Q10 and the useful life were determined by the linear regression equation of Labuza, obtaining for Mesophilic Aerobics in treatments 6 (17.7 t), 8 (21 t), with t (days), treatment 2 the behavior was linear and 4 was decreasing but the count did not exceed the allowed limit, the treatments (1-3-5-7) presented contamination, for E. Coli the treatment 3 presented (2.8 t) the treatments (1- 7), presented contamination, while in the treatments (2-4-5-6-8) absences were found. The behavior of Staphilococus Aureus treatments 1 (9,02 t), 4 (2.0 t) treatment and 7 (8.1 t), in the treatments (3-5) there was contamination, while in the treatments ( 2-6-8) exceed the limit, the analysis of salmonella spp presented absence, so that treatment 4 presented the best conditions, through a sensory analysis the acceptability of this was established, obtaining a color score (1.9) odor (1,7), taste and texture (2,2) and general appearance (2,1).